Remoção de matéria orgânica em sistemas de lagoas de estabilização no Nordeste brasileiro - Silva, Odênia Alves de Lima (2011)
Stabilization pond is the main technology used for treatment wastewater, in northeast Brazil, due to lower cost of deployment, operation and maintenance compared to other technologies. Most systems of stabilization ponds has been in operation for some time, on average 10 years of operation, receiving high organic loads and do not have good removal efficiencies of the main parameters for which have been designed. Therefore it is necessary to work to quantify the efficiency of current systems. This study evaluated the biodegradability of organic matter in raw sewage, the removal of organic matter in reactors and determination of the kinetic constant removal of organic matter (k), both in reactors and in raw sewage, based on the analysis made in the laboratory and through mathematical methods proposed in the literature, in nine systems stabilization ponds, located in Rio Grande do Norte. In relation the degradation kinetics in stabilization ponds, it was observed that many papers published in the literature were obtained in pilot-scale systems, which often, due to the action of external factors such as wind and temperature, these can t be considered as a reference in the analysis of the kinetic constant K, so the need for more research into systems of scale. This study had three distinct phases and simultaneous, routine monitoring, study of the daily cycle and the determination of kinetic constant of degradation of organic matter (K). The monitoring showed that the removal efficiencies of organic matter on most systems were lower than suggested by the literature, the best efficiencies of around 76% (BOD) and 72% (COD) and the worst of the order of 48% (BOD) and 55% (COD). The calculation of K in raw sewage (Ke) was within the range of variation expected in the literature (0.35 to 0.60 days-1). Already for the results obtained for K in the reactors (Kr), there were well below the values recommended in the literature (0.25 to 0.40 d-1 for complete mix and from 0.13 to 0.17 d-1 for flow dispersed), in line with the overloads that organic systems are subject